2017
DOI: 10.1590/0103-8478cr20151216
|View full text |Cite
|
Sign up to set email alerts
|

Complementing firewood with alternative energy sources in Rio Pardo Watershed, Brazil

Abstract: Wood is the primary energy source for grains and Tobacco drying in the Rio Pardo Watershed (RPW). The amount of firewood produced in the RPW is not enough to supply the demand. Recently, an automatized supply system was introduced in the region enabling the use of sawdust and pellets. In this context, this study aims to compare firewood, sawdust and pellets as energy sources for Tobacco curing in air-forced curing systems. Energetic density was used to estimate the biomass consumption in Tobacco curing. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…A study carried out on a forced air curing unit of tobacco growers in southern Brazil, showed a consumption of Eucalyptus sp. firewood in the range of 3.96 kg per kg of tobacco [15], a value higher than that verified in this research. The curing unit capacity was not available in the study for comparison; however, the firewood moisture and forest species used may partially explain the difference in results.…”
Section: Efficiency In Biomass Consumptioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A study carried out on a forced air curing unit of tobacco growers in southern Brazil, showed a consumption of Eucalyptus sp. firewood in the range of 3.96 kg per kg of tobacco [15], a value higher than that verified in this research. The curing unit capacity was not available in the study for comparison; however, the firewood moisture and forest species used may partially explain the difference in results.…”
Section: Efficiency In Biomass Consumptioncontrasting
confidence: 72%
“…Particles and gases derived from incomplete combustion are among the main environmental and health problems, reinforcing the need to study the relationship between biofuel consumption and GHG emissions. Currently, some studies allow verifying how pollutant gas emissions behave with the use of firewood in grain drying [11,12] and the importance of using forest biomass in the energy generation process, both with the use of firewood [13,14] and pellets [15,16]. However, to the best of our knowledge, the combination of the technological level of drying units with the type of biomass consumed, the resultant biomass consumption, and GHG emissions have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the improvement of thermal efficiency of biomass fuel should be based on "uniform fuel size + secondary combustion of gasified gas + precise control of feed" in the process of fuel heating. Energetic density is an important factor affecting the thermal efficiency of flue-cured tobacco [36]. In this work, the diameter and length of the biomass pellets are 10 mm and 30-50 mm, respectively; thus, it is necessary to use this new BBF burner to study the thermal efficiencies of the different diameters and lengths of pellets used for heating TC.…”
Section: Comparison Between Conventional and Biomass Curing Techniquesmentioning
confidence: 99%
“…With technological advances increasing the use of combustion technology using BPF burners for flue-cured tobacco heating (FTH), a growing number of flue-cured-tobacco-producing countries and regions have begun to transition from fossil fuels to biomass fuel as their primary tobacco-curing heat source [2,3]. Through the analysis of various heat sources in the agricultural field of flue-cured tobacco production, previous studies have indicated that BPT offers an optimal method to realize the green production of flue-cured tobacco [4][5][6].…”
Section: Introductionmentioning
confidence: 99%